2023
DOI: 10.3390/microorganisms11030666
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dengue Virus Serotypes 1&2 with Severe Dengue Having Deletions in Their 3′Untranslated Regions (3′UTRs)

Abstract: Dengue virus infections are recorded as hyper-endemic in many countries, including India. Research pertaining to the reasons for frequent outbreaks and severe dengue is ongoing. Hyderabad city, India, has been recorded as a ‘hotspot’ for dengue virus infections. Dengue virus strains circulating over the past few years in Hyderabad city have been characterized at the molecular level to analyze the serotype/genotypes; 3′UTRs were further amplified and sequenced. The disease severity in patients infected with den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…5C1-CN4 was observed to have transmitted de nitely locally in Guangzhou from 2013 to 2015. The 5C/5C1 strains, which exhibits a 21nt-dHVR-3'-UTR deletion, was initially identi ed in India [29] and subsequently played a pivotal role in the signi cant outbreaks that occurred in Singapore (2013) [23] and China (2014). Furthermore, by discriminating the two lineages of 5C1, it was found that Lineage 1 was originated from India, and Lineage 2 was traced back to Singapore.…”
Section: Discussionmentioning
confidence: 99%
“…5C1-CN4 was observed to have transmitted de nitely locally in Guangzhou from 2013 to 2015. The 5C/5C1 strains, which exhibits a 21nt-dHVR-3'-UTR deletion, was initially identi ed in India [29] and subsequently played a pivotal role in the signi cant outbreaks that occurred in Singapore (2013) [23] and China (2014). Furthermore, by discriminating the two lineages of 5C1, it was found that Lineage 1 was originated from India, and Lineage 2 was traced back to Singapore.…”
Section: Discussionmentioning
confidence: 99%